Synthesis, in-vitro inhibition of cyclooxygenases and in silico studies of new isoxazole derivatives - Alam, Waqas; Khan, Haroon; Saeed Jan, Muhammad; Rashid, Umer; Abusharha, Ali; Daglia, Maria (Frontiers in Chemistry, 2023)
Isoxazole belongs to the class of five-member heterocyclic compounds. The process of developing new drugs has significantly gained attention due to inadequate pharmacokinetic and safety attributes of the available drugs. This study aimed to design a new diverse array of ten novel isoxazole derivatives via Claisen Schmidt condensation reaction. In vitro COX-1/2 anti-inflammatory assay, in silico studies of potent compounds, MD simulation and SwissADME pharmacokinetic profile were investigated in this research. The in vitro COX-1 and COX-2 enzymes inhibitory assay showed that almost all the tested compounds exhibited anti-inflammatory effect whereas C6, C5 and C3 were found most potent COX-2 enzymes inhibitor amongst the tested compounds and are good candidates for selective COX-2 inhibitors. The binding orientations and binding energy results also showed the selectivity of compounds towards COX-2. Physicochemical properties, pharmacokinetic profile, lipophilicity, water solubility, drug metabolism, drug likeness properties and medicinal chemistry of the synthesized isoxazole derivatives were assessed. The SwissADME data base was used to assess the physicochemical properties and drug likeness properties of the synthesized isoxazole derivatives. All the compounds were shown high GI absorption except Compound (C7). Compound 1 (C1) and Compound 2 (C2) were found to cross the blood brain barrier (BBB). The Lipinski's rule of five is not violated by any of the ten synthesized isoxazole derivatives. It was predicted with SwissADME data base that C2, C5, C6, C7 and C8 are potent inhibitors of cytochrome (CYP) subtype CYP-2C19. Subtype of CYP-2C9 was inhibited by C4 and C7. The medicinal chemistry of all the compounds C1-C10 showed no PAIN (Pan assay interference compounds) alerts. The improved gastrointestinal (GI) absorption and BBB permeability of C1 and C2 can provide a future prospective for new researchers in the medicinal field to investigate the compounds for the management of chronic diseases. The synthesized isoxazole compounds showed excellent in vitro COX-1/2 enzymes anti-inflammatory investigations, in silico studies, good physicochemical properties, and improved pharmacokinetic profile which will be further investigated via in vivo anti-inflammatory activities. Moreover, to further support our findings of the computational research and in vitro studies, an in-vivo pharmacokinetic profile is suggested in the future.